The Role of Social Media in Disseminating Agronomic Information and Empowering Farmers - Maria Goretti Meity Polii; Romi Mesra (PT. NALURI EDUKASI PRESS, 2024)
This study aims to explore the role of social media in agronomic information dissemination and farmer empowerment. Using a systematic literature review method, this study analyzes current research on the use of social media in the agricultural context. The results show that social media has significantly improved farmers' access to agronomic information, accelerated the adoption of agricultural innovations, and facilitated the formation of virtual farmer communities. Platforms such as Facebook, WhatsApp, and YouTube have become the main channels for sharing agricultural knowledge and accessing markets. However, challenges such as the digital divide and information reliability still need to be addressed. The study concludes that social media has great potential for transforming the agricultural sector, but requires an integrated approach involving improving digital infrastructure, developing farmers' digital literacy, and multi-stakeholder collaboration to optimize its benefits.